Dynamic emission Stokes shift and liquid-like dielectric solvation of band edge carriers in lead-halide perovskites - Yinsheng Guo (Nature Portfolio, 2019)
Lead halide perovskites have unique electronic properties that depend on the crystal’s anharmonicity. Dielectric solvation theories, developed for molecules dissolved in polar liquids, are shown here to reproduce the temperature behavior of carrier solvation in the electronic spectra, implying strongly anharmonic lattice dynamics.